Design of robust control and monitoring system for microgrid stabilization - Vachirasricirikul, Sitthidet; Ngamroo, Issarachai; Kaitwanidvilai, Somyot; Chaiyatham, Theerawut (My University, 2009)
This paper proposes a design of the robust control and monitoring system (RCMS) for stabilization of microgrid (MG) system. The power sources in MG consists of wind power (WP), photovoltaic (PV), micro-turbine (MT) and fuel cell (FC). Due to intermittent powers from WP, PV and load fluctuations, the MG stabilization of RCMS is performed by controlling the power outputs of MT and electrolyzer system (ES) in both islanding and interconnected utility grid operations. The structure of MT and ES controllers is the proportional integral (PI). By taking system uncertainties into account, control parameters of MT and ES are simultaneously optimized based on the particle swarm optimization (PSO) based fixed-structure H∞ loop shaping control. Simulation results show the robustness and effectiveness of the proposed RCMS against the variation of system parameters and operating conditions. ©2009 IEEE.
Keywords: H∞ loop shaping control; Microgrid; Particle swarm optimization; Robust control